Persepsi Pengguna terhadap Kinerja Sistem Pembayaran Tiket dalam Mendukung Manajemen Keuangan BRT Trans Jateng - Adelia Hidayatunnisa; Enik Rahayu (Mahesa Research Center, 2026)
This article aims to analyze users’ perceptions and satisfaction with the performance of the ticket payment system in supporting the financial management of BRT Trans Jateng. The problem is focused on the extent to which the non-cash payment system is able to meet users’ expectations while functioning as an instrument for control, transparency, and efficiency in public transportation financial management. To address this issue, the study adopts an integrative approach based on the Technology Acceptance Model, user satisfaction theory, and public sector financial management concepts. Data were collected through in-depth interviews with users and managers of BRT Trans Jateng, field observations, and supporting documentation, and were analyzed qualitatively using a thematic analysis approach. The findings indicate that the performance of the non-cash payment system not only shapes user satisfaction through aspects of convenience, speed, and security, but also contributes to enhancing transparency and accuracy in financial management. This study reveals that the integration between payment system performance and financial management functions is a key factor in improving the quality of public transportation services. The novelty of this research lies in the integration of user satisfaction and financial management perspectives within a unified analytical framework, which have previously been examined separately. This study concludes that the BRT Trans Jateng ticket payment system functions not only as a transaction tool but also as a strategic mechanism supporting effective and sustainable financial governance.